Molecular mechanisms and therapeutic applications of huaier in breast cancer treatment - Luo, Ke-fei; Zhou, Lin-xi; Wu, Zi-wei; Tian, Yuan; Jiang, Jun; Wang, Ming-hao (Frontiers in Pharmacology, 2024)
Breast cancer is one of the most common female malignant tumors today and represents a serious health risk for women. Although the survival rate and quality of life of patients with breast cancer are improving with the continuous development of medical technology, metastasis, recurrence, and drug resistance of breast cancer remain a significant problem. Huaier, a traditional Chinese medicine(TCM) fungus, is a type of Sophora embolism fungus growing on old Sophora stems. The polysaccharides of Trametes robiniophila Murr (PS-T) are the main active ingredient of Huaier. There is increasing evidence that Huaier has great potential in breast cancer treatment, and its anticancer mechanism may be related to a variety of biological activities, such as the inhibition of cell proliferation, metastasis, tumor angiogenesis, the promotion of cancer cell death, and regulation of tumor-specific immunity. There is growing evidence that Huaier may be effective in the clinical treatment of breast cancer. This review systematically summarizes the basic and clinical studies on the use of Huaier in the treatment of breast cancer, providing useful information to guide the clinical application of Huaier and future clinical studies.